Positive cardiovascular health: longitudinal investigation of sustained health behavior in a cross-lagged model - Ocsovszky, Zsofia; Ehrenberger, Blanka; Berenyi, Blanka; Assabiny, Alexandra; Otohal, Jozsef; Martos, Tamas; Papp-Zipernovszky, Orsolya; Hegedus, Fanni; Merkely, Bela; Csabai, Marta; Bagyura, Zsolt (Frontiers in Public Health, 2024)
Objective: Our study focuses on the role of psychological states in the development of cardiovascular disease (CVD) and explores the potential of positive psychological factors in reducing CVD risk. While existing research has predominantly examined negative mental states and risk behaviour, this longitudinal study takes a novel approach by investigating positive psychological well-being and its impact on sustained health behaviour. Method: The research involved participants (n = 502) with medium to high cardiovascular risk who underwent a comprehensive risk assessment in 2012, followed by written risk communication. Health behaviour and psychological variables were measured in 2012 and 2019. A cross-lagged model was employed to repeat measures of a cardiovascular health index with latent factors. Results: Results indicated an excellent fit for the model (RMSEA = 0.0644, CFI = 0.936, TLI = 0.921, SRMR = 0.050), with significant associations between the observed variables (p < 0.05) and created latent factors. Furthermore, the model implied significant bivariate correlations (p < 0.05) between latent constructs of sustained health behaviour and positive psychological states in 2012 and 2019. A significant regression relationship between Health Awareness Index 2012 and 2019, between Psychological well-being in 2012 and 2019 (B=1.103 p=0.038), latent factors could be identified (B=1.103 p=0.038) using cross-lagged panel model. Results highlighted the importance of cardiovascular health awareness, subjective risk perception, and self-directed efforts in facilitating health behavior change. Based on the results mentioned above it emphasised the importance of cardiovascular health awareness, subjective risk perception, and self-directed efforts in facilitating health behaviour change. Conclusion: The study demonstrated bidirectional relationships between, health consciousness, and long-term changes in health behaviour. Relationships between psychological well-being and health awareness emphasise that 1 Ocsovszky et al. Positive Cardiovascular Health in a Cross-Lagged Model positive experiences and reinforcement are crucial in sustaining optimal health behaviour. Our findings offer a new perspective on cardiovascular risk screening and prevention interventions.Extending cardiovascular risk screening with psychological measures may broaden prevention opportunities by including psychological elements reinforcing positive psychological states. The findings suggest that an effective prevention program must consider stabilising and maintaining positive psychological states to achieve lasting improvements in cardiovascular health.